Viri in pouk zgodovine - Potočnik, Dragan (2013)
Sources and Lessons of History. This book clearly and systematically presents the diverse resources that history teachers have at their disposal to deliver history lessons in primary and secondary schools. In the book, historical sources are divided into material sources, written sources, literary sources with historical content, oral sources, image sources and contemporary media sources. All resources highlight the positives and the potential for classroom use. There is also an emphasis on meeting young people with resources outside the school premises (excursions, visiting a museum, an archive and a hometown). A special feature is secondary written sources, where the author chooses examples of descriptions that non-European teachers can use to address the subject matter. Examples of literary texts and oral sources (folk songs and fairy tales, customs and customs) can also be used to better understand selected historical content. Painting sources highlight paintings, sculptures and architectural works, photographs, postcards, caricatures, posters and maps, where the author demonstrates the reasonableness of use on examples from local history or non-European history. Contemporary media and sources are also gaining ground, and the author is also evaluating films, the Internet and other electronic materials that can be used effectively in history. Through the transparency of various sources, the author proves that it is precisely the sources that enable greater visibility and picturesqueness of the historical past.